Moral anxiety among secondary school students (Journal of the College of Education for Women, 2019)
Research targeted availability of moral anxiety among secondary school students. The research sample consisted of 500 students from the (fifth grade secondary school) scientific and literary branches.The researcher prepared a measure of moral anxiety which is in its final form of (36) items. The researcher analyzed the data statistically, significant results showed that the sample of the research they have a moral anxiety .From these results the researcher came up with a number of recommendations and proposals.